Interface engineering for a rational design of poison-free bimetallic CO oxidation catalysts. Issue 16 (11th April 2017) - Shin, Kihyun; Zhang, Liang; An, Hyesung; Ha, Hyunwoo; Yoo, Mi; Lee, Hyuck Mo; Henkelman, Graeme; Kim, Hyun You
Abstract : CO-poisoning free bimetallic CO oxidation catalysts are proposed based on the density functional theory study of Pt–Cu bimetallic nanoparticles. Abstract : We use density functional theory calculations of Pt@Cu core@shell nanoparticles (NPs) to design bifunctional poison-free CO oxidation catalysts. By calculating the adsorption chemistry under CO oxidation conditions, we find that the Pt@Cu NPs will be active for CO oxidation with resistance to CO-poisoning. The CO oxidation pathway at the Pt–Cu interface is determined on the Pt NP covered with a full- and partial-shell of Cu. The exposed portion of the Pt core preferentially binds CO and the Cu shell binds O2, supplying oxygen for the reaction. The Pt–Cu interface provides CO-oxidation sites that are not poisoned by either CO or O2 . Additional computational screening shows that this separation of reactant binding sites is possible for several other core@shell NPs. Our results indicate that the metal–metal interface within a single NP can be optimized for design of bifunctional catalytic systems with improved performance.